Are Real Effects of Credit Supply Overestimated? Bias from Firms' Current Situation and Future Expectations - Michael Kleemann; Manuel Wiegand (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2014)
This paper advocates for incorporating timely measures of firms' current situation and future expectations when disentangling real effects of credit supply from demand-side factors. Identification of supply-side effects in firm-level analyses often relies on balance sheet variables to control for firm heterogeneity. While balance sheets mirror past business, bias from contemporaneous and forward-looking firm-side factors may persist.Using German firm-level survey data from 2003 to 2011, we show that controllingfor firms' current situation and future expectations reduces upward bias in estimatedcredit supply-side effects on firm-level production. This is particularly important when market data is unavailable for firms.
Keywords: G21; E23; L25; 330; Credit constraints; production; employment; matching estimator